Action potentials: extrapolating an ideology from the Anonymous hacker socio-political movement (a qualitative meta-analysis) - Hai-Jew, Shalin (Information Science Reference, 2013)
An ideology is defined as a set of ideas that “explains and evaluates social conditions, helps people understand their place in society, and provides a program for social and political action” (Ball & Dagger, 2011, p. 4). As such, these concepts underpin the actions of various groups and organizations, including that of the Anonymous hacker group, which professes no ideology or creed. Rather, the group has styled itself as a kind of anarchic global brain connected by various spaces on the Internet. This work explores four main data streams to extrapolate the group’s ideology: the current socio-political context of hacking and hacktivism; the group’s self-definition (through its professed values); the group’s actions (through the “propaganda of the deed”); and the insights of others about the group This chapter defines the socio-technical context of this Anonymous hacker socio-political movement, which draws ideas from the Hacker Manifesto 2.0, which suggests the advent of a new economic system with the new technological vectors (mediums of communication). This movement is apparently pushing forth the advent of a new information regime in which the abstraction of ideas adds a “surplus” economic value that may be tapped. Styled as fighters against government tyranny, they are pushing hard against an international regime of intellectual property and information control by governments and corporations. This is being published in the spirit that (some) information wants to be free and that there is a value in direct discourse.
Keywords: Anonymous hacker group; Hacktivism; Socio-political activism; Hacker Manifesto 2.0